1982
DOI: 10.1128/aem.44.1.23-27.1982
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Coal by the Fungi Polyporus versicolor and Poria monticola

Abstract: We report that two species of basidiomycete fungi ( Polyporus versicolor and Poria monticola ) grow in minimal liquid or solid medium when supplemented with crushed lignite coal. The fungi also grow directly on crushed lignite coal. The growth of both fungi was observed qualitatively as the production and extension of hyphae. No fungal growth occurred in minimal agar medium without coal. The fungi degraded solid lignite coal to a black liquid product which never … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(42 citation statements)
references
References 10 publications
2
40
0
Order By: Relevance
“…Bioconversion of coal by fungi has been the subject of thorough investigation since the early 1980s [1][2][3][4][5][6][7][8][9][10][11]. A wide range of bioconversion mechanisms are used by fungi and these include biosolubilization [9,12,13], liquefaction [14,15], and depolymerization [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Bioconversion of coal by fungi has been the subject of thorough investigation since the early 1980s [1][2][3][4][5][6][7][8][9][10][11]. A wide range of bioconversion mechanisms are used by fungi and these include biosolubilization [9,12,13], liquefaction [14,15], and depolymerization [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, they found that when the fungal spores germinated, there was no affinity to the coal, but in mature stage many coal particles adhered to the fungal cell wall and the older hyphae became completely coated with the coal layer. Cohen and Gabriele (1982) found that the two white rot fungi, Trametes versicolor and Poria monticola were able to convert leonardite, a low rank coal deposit in North Dakota. Few more researchers have also shown that the fungi and actinomycetes are able to solubilise small amount of 3.2 N nitric acid oxidized coals in liquid culture (Quigley et al, 1988).…”
Section: Microbial Degradation Of Coalmentioning
confidence: 99%
“…Some coals (mostly low-rank and in some cases bituminous coals) have the potential to be solubilized by the action of microorganisms [7]. There are several microorganisms, from different taxa, for which a coal solubilization capability was demonstrated ( Table 17).…”
Section: Fungi or Actinomycetesmentioning
confidence: 99%